Rola zachowań prozdrowotnych w utrzymaniu zdrowia kobiet. Wyniki badań pilotażowych - Hildt-Ciupińska, Katarzyna; Pawłowska-Cyprysiak, Karolina (Kultura-Społeczeństwo-Edukacja, 2024)
Lifestyle is considered one of the most important determinants of health, which most of of us can influence and consciously modify it. However, it is essential to raise health awareness among people so that they know how to do it effectively. The workplace is one of the settings for health promotion, which fosters the spread of health knowledge and care among different groups of people – both men and women, with different levels of education, of different ages, doing different types of work. Women, given their life cycle, from puberty to procreation to menopause, are a specific group from the point of view of health and taking care of it. They are also a special group, given the many burdens of their social roles. All this contributes to the diverse health needs of women of different ages, but also numerous risk factors, including the risk of certain diseases. It is therefore necessary to carry out health education for women, taking into account their age, the type of work they do and their non-work burdens. The purpose of this article is to present the results of a preliminary-pilot study on the health care of active women.